1997
DOI: 10.1159/000237596
|View full text |Cite
|
Sign up to set email alerts
|

IgG and IgE Antibodies in Subjects Allergic to Penicillins Recognize Different Parts of the Penicillin Molecule

Abstract: Background: IgE and IgG antibodies to penicillins can have different specificities. However, this response, including the recognition of the different parts of penicillin, has never been studied in the same subject. Objective: Study of the specificity of IgE and IgG antibodies and the relevant parts of the penicillin molecule that contribute to the hapten binding site in sera from human. Methods: Specific IgE antibodies were determined by RAST and specific IgG antibodies by ELISA. The recognition of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…12 Although we present a limited number of cases, it is of note that the delayed skin test intradermal response was negative. Concerning the T-cell response, these result are not surprising, and the low sensitivity of skin testing in T-cellemediated reactions has been reported.…”
Section: Discussionmentioning
confidence: 67%
“…12 Although we present a limited number of cases, it is of note that the delayed skin test intradermal response was negative. Concerning the T-cell response, these result are not surprising, and the low sensitivity of skin testing in T-cellemediated reactions has been reported.…”
Section: Discussionmentioning
confidence: 67%
“…These have been detected in certain individuals [15,16] and it has been demonstrated that anti-penicillin antibody titers rise rapidly during desensitization and then decline slowly with time [15]. The speed of the response in desensitized patients would be in keeping with a secondary antibody response.…”
Section: Discussionmentioning
confidence: 97%
“…They influence the T-cell response by enhancing antigen capture and delivery by modulating processing pathways, thus suppressing the generation of dominant antigenic determinants and by preventing processing (Watts and Lanzavecchia, 1993). We and others have used drug-protein conjugates to detect anti-drug antibodies in certain tolerant and allergic patients (de Haan et al, 1986;Christie et al, 1988;Daftarian et al, 1995;Torres et al, 1997). However, the dynamics of the drug antigen-specific humoral response and the kinetics of antibody production have not been defined.…”
Section: A An Overview Of the Immune Responsementioning
confidence: 99%
“…It is possible that this pathway of drug-specific T-cell activation is an in vitro artifact mimicking the action of processed haptenmodified peptides. Importantly, several groups have used b-lactam albumin conjugates to detect antidrug antibodies in tolerant and allergic patients (de Haan et al, 1986;Christie et al, 1988;Torres et al, 1997). Thus, hapten theory is thought to accurately describe the drug-specific activation of B cells that recognize protein antigens directly through their B cell receptor.…”
Section: The Antigenicity and Immunogenicity Of Directly Reactive mentioning
confidence: 99%